Continuous Infusion of Flumazenil in the Management of Benzodiazepines Detoxification - Benini, Anna; Gottardo, Rossella; Chiamulera, Cristiano; Bertoldi, Anna; Zamboni, Lorenzo; Lugoboni, Fabio (Frontiers in Psychiatry, 2021)
An effective approach in the treatment of benzodiazepine (BZD) overdosing and detoxification is flumazenil (FLU). Studies in chronic users who discontinued BZD in a clinical setting suggested that multiple slow bolus infusions of FLU reduce BZD withdrawal symptoms. The aim of this study was to confirm FLU efficacy for reducing BZD withdrawal syndrome by means of continuous elastomeric infusion, correlated to drugs plasma level and patients' compliance. Methods: Seven-day FLU 1 mg/day subcutaneously injected through an elastomeric pump and BZDs lormetazepam, clonazepam, and lorazepam were assessed by HPLC-MS/MS in serum of patients before and after 4 and 7 days of FLU continuous infusion treatment. Changes in withdrawal severity were assessed by using the BZD Withdrawal Scale (BWS). Results: Fourteen patients (mean age ± SD 42.5 ± 8.0 years, 5 male and 9 female), admitted to the hospital for high-dose BZD detoxification, were enrolled in the study. Serum FLU concentrations significantly decreased from 0.54 ± 0.33 ng/ml (mean ± SD) after 4 days of treatment to 0.1 ± 0.2 ng/ml at the end of infusion. Lormetazepam concentrations were 502.5 ± 610.0 ng/ml at hospital admission, 26.2 ± 26.8 ng/ml after 4 days, and 0 at the end of treatment. BWS values decreased during FLU treatment temporal period. FLU was well-tolerated by patients. Conclusions: Elastomeric FLU infusion for BZD detoxification is a feasible administration device to maintain adequate, constant, and tolerated FLU concentrations for reducing BZD withdrawal symptoms.